Inflammasome-Dependent Peroxiredoxin 2 Secretion Induces the Classical Complement Pathway Activation - Park, Cheol Ho; Lee, Hyun Sook; Kwak, Man Sup; Shin, Jeon-Soo (Immune network, 2021)
Peroxiredoxins (Prxs) are ubiquitously expressed peroxidases that reduce hydrogen peroxide or alkyl peroxide production in cells. Prxs are released from cells in response to various stress conditions, and they function as damage-associated molecular pattern molecules. However, the secretory mechanism of Prxs and their roles have not been elucidated. Thus, we aimed to determine whether inflammasome activation is a secretory mechanism of Prxs and subsequently identify the effect of the secreted Prxs on activation of the classical complement pathway. Using J774A.1, a murine macrophage cell line, we demonstrated that NLRP3 inflammasome activation induces Prx1, Prx2, Prx5, and Prx6 secretion in a caspase-1 dependent manner. Using HEK293T cells with a transfection system, we revealed that the release of Prx1 and Prx2 relies on gasdermin-D (GSDMD)-mediated secretion. Next, we confirmed the binding of both Prx1 and Prx2 to C1q; however, only Prx2 could induce the C1q-mediated classical complement pathway activation. Collectively, our results suggest that inflammasome activation is a secretory mechanism of Prxs and that GSDMD is a mediator of their secretion. Moreover, secreted Prx1 and Prx2 bind with C1q, but only Prx2 mediates the classical complement pathway activation.Peroxiredoxins (Prxs) are ubiquitously expressed peroxidases that reduce hydrogen peroxide or alkyl peroxide production in cells. Prxs are released from cells in response to various stress conditions, and they function as damage-associated molecular pattern molecules. However, the secretory mechanism of Prxs and their roles have not been elucidated. Thus, we aimed to determine whether inflammasome activation is a secretory mechanism of Prxs and subsequently identify the effect of the secreted Prxs on activation of the classical complement pathway. Using J774A.1, a murine macrophage cell line, we demonstrated that NLRP3 inflammasome activation induces Prx1, Prx2, Prx5, and Prx6 secretion in a caspase-1 dependent manner. Using HEK293T cells with a transfection system, we revealed that the release of Prx1 and Prx2 relies on gasdermin-D (GSDMD)-mediated secretion. Next, we confirmed the binding of both Prx1 and Prx2 to C1q; however, only Prx2 could induce the C1q-mediated classical complement pathway activation. Collectively, our results suggest that inflammasome activation is a secretory mechanism of Prxs and that GSDMD is a mediator of their secretion. Moreover, secreted Prx1 and Prx2 bind with C1q, but only Prx2 mediates the classical complement pathway activation.